Association between age‐related reductions in testosterone and risk of prostate cancer—An analysis of patients' data with prostatic diseases. Issue 9 (24th July 2017) - Wang, Kai; Chen, Xinguang; Bird, Victoria Y.; Gerke, Travis A.; Manini, Todd M.; Prosperi, Mattia
Abstract : The relationship between serum total testosterone and prostate cancer (PCa) risk is controversial. The hypothesis that faster age‐related reduction in testosterone is linked with increased PCa risk remains untested. We conducted our study at a tertiary‐level hospital in southeast of the USA, and derived data from the Medical Registry Database of individuals that were diagnosed of any prostate‐related disease from 2001 to 2015. Cases were those diagnosed of PCa and had one or more measurements of testosterone prior to PCa diagnosis. Controls were those without PCa and had one or more testosterone measurements. Multivariable logistic regression models for PCa risk of absolute levels (one‐time measure and 5‐year average) and annual change in testosterone were respectively constructed. Among a total of 1, 559 patients, 217 were PCa cases, and neither one‐time measure nor 5‐year average of testosterone was found to be significantly associated with PCa risk. Among the 379 patients with two or more testosterone measurements, 27 were PCa cases. For every 10 ng/dL increment in annual reduction of testosterone, the risk of PCa would increase by 14% [adjusted odds ratio, 1.14; 95% confidence interval (CI), 1.03–1.25]. Compared to patients with a relatively stable testosterone, patients with an annual testosterone reduction of more than 30 ng/dL had 5.03 [95% CI: 1.53, 16.55] fold increase in PCa risk. This implies a faster age‐related reduction in, but not absolute level of serum total testosterone as a risk factor for PCa. Further longitudinal studies are needed to confirm this finding. Abstract : What's new? While serum testosterone levels in males decline markedly with age, particularly after age 40, risk of prostate cancer increases. Hypotheses have suggested a causal relationship, though whether serum testosterone levels are related to prostate cancer risk remains uncertain. In this analysis of absolute serum testosterone levels (one‐time measure and 5‐year average) and age‐related annual changes in serum total testosterone, higher age‐related annual reductions, rather than absolute testosterone levels, was associated with increased prostate cancer risk. The findings support a role for testosterone reduction in prostate cancer and suggest that slowing age‐related testosterone decline may be relevant to prostate cancer prevention.